Leveraging the future of diagnosis and management of diabetes: From old indexes to new technologies. (22nd December 2022) - Meneses, Maria João; Patarrão, Rita Susana; Pinheiro, Tomás; Coelho, Inês; Carriço, Nuno; Marques, Ana Carolina; Romão, Artur; Nabais, João; Fortunato, Elvira; Raposo, João Filipe; Macedo, Maria Paula
Abstract: Background: Diabetes is a heterogeneous and multifactorial disease. However, glycemia and glycated hemoglobin have been the focus of diabetes diagnosis and management for the last decades. As diabetes management goes far beyond glucose control, it has become clear that assessment of other biochemical parameters gives a much wider view of the metabolic state of each individual, enabling a precision medicine approach. Methods: In this review, we summarize and discuss indexes that have been used in epidemiological studies and in the clinical practice. Results: Indexes of insulin secretion, sensitivity/resistance and metabolism have been developed and validated over the years to account also with insulin, C‐peptide, triglycerides or even anthropometric measures. Nevertheless, each one has their own objective and consequently, advantages and disadvantages for specific cases. Thus, we discuss how new technologies, namely new sensors but also new softwares/applications, can improve the diagnosis and management of diabetes, both for healthcare professionals but also for caretakers and, importantly, to promote the empowerment of people living with diabetes. Conclusions: In long‐term, the solution for a better diabetes management would be a platform that allows to integrate all sorts of relevant information for the person with diabetes and for the healthcare practitioners, namely glucose, insulin and C‐peptide or, in case of need, other parameters/indexes at home, sometimes more than once a day. This solution would allow a better and simpler disease management, more adequate therapeutics thereby improving patients' quality of life and reducing associated costs.